2016
DOI: 10.1158/1078-0432.ccr-15-1136
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab in Resected and Unresectable Metastatic Melanoma: Characteristics of Immune-Related Adverse Events and Association with Outcomes

Abstract: Purpose Retrospective analysis of irAEs in melanoma patients treated with nivolumab. Experimental Design Data were pooled from 148 patients (33 resected, 115 unresectable) treated with nivolumab plus peptide vaccine or nivolumab alone every 2 weeks for 12 weeks. Patients with stable disease or regression received an additional 12-week cycle, then nivolumab alone every 12 weeks for up to 2 additional years. Frequency, grade, and characteristics of irAEs were analyzed. A 12-week landmark survival analysis usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
573
4
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(673 citation statements)
references
References 51 publications
65
573
4
9
Order By: Relevance
“…4,5,7,8 An association between appearance of skin irAEs and OS in melanoma has been reported. [13][14][15]17 Similarly, our data suggest an association between skin irAEs and tumor response. The histological analysis of the rashes on the one hand allowed us to rule out clinical differential diagnoses of eczema and psoriasis and on the other hand revealed that the rashes were characterized by an inflammation rich in CD3C T-lymphocytes.…”
Section: Discussionsupporting
confidence: 79%
“…4,5,7,8 An association between appearance of skin irAEs and OS in melanoma has been reported. [13][14][15]17 Similarly, our data suggest an association between skin irAEs and tumor response. The histological analysis of the rashes on the one hand allowed us to rule out clinical differential diagnoses of eczema and psoriasis and on the other hand revealed that the rashes were characterized by an inflammation rich in CD3C T-lymphocytes.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, both vitiligo and/or cutaneous reactions emerging during nivolumab treatment in patients with melanoma have recently been reported to be associated with overall survival (23). As a consequence, cutaneous reactions during anti-PD-1 treatment could potentially be used as biomarkers in the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that patients may still respond to immune checkpoint blockade despite the development of adverse events, the administration of corticosteroids or the cessation of treatment [44] . Intriguingly, the development of immune-related adverse events, particularly rash and vitiligo, has even been associated with improved disease outcome in melanoma patients treated with anti-PD-1 [47] , suggesting that the breaking of tolerance to local (auto-) antigens may also lead to improved anti-tumor immune responses. Figure 1 shows the visualization of treatmentassociated adverse events and their anatomical sites in melanoma patients treated with anti-PD-1 and/or anti-CTLA-4, as reported by Larkin and colleagues [37] .…”
Section: Treatment-related Adverse Events and Their Managementmentioning
confidence: 99%
“…Th1-and CTLA-4-related gene expressions within the tumor prior to treatment have been linked to subsequent response to anti-PDL-1 [47] . In another study, melanoma patients responding successfully to anti-PD-1 treatment were more likely to display high [37] TGF-β levels pre-treatment and an expanded IL-9 producing CD4 + T (Th9) cell compartment posttreatment [52] .…”
Section: Predicting the Efficacy Of Anti-pd-1/ Ctla-4 Treatmentsmentioning
confidence: 99%